Existing gap between the curriculum mesh of the Industrial Engineering career of the Universidad Hispanoamericana with respect to two Latin American TOP5 universities that refer to the Washington Agreement - Ramírez-Mora, Hector Jesús (2023)
The Industrial Engineering career of the Universidad Hispanoamericana (UH), after obtaining its accreditation with the SINAES in May 2022, seeks to continue improving its offer and by comparing it with other equivalent academic programs that have the accreditation of the Washington Agreement. or its equivalent through mutual recognition agreements with other market standards; to use the gaps detected and solve them. This time the comparison is made with two TOP5 universities in the QS ranking of the year 2022.